Patterns and correlates of claims for brown bear damage on a continental scale. Issue 1 (24th June 2016) - Bautista, Carlos; Naves, Javier; Revilla, Eloy; Fernández, Néstor; Albrecht, Jörg; Scharf, Anne K.; Rigg, Robin; Karamanlidis, Alexandros A.; Jerina, Klemen; Huber, Djuro; Palazón, Santiago; Kont, Raido; et al.
Summary: Wildlife damage to human property threatens human–wildlife coexistence. Conflicts arising from wildlife damage in intensively managed landscapes often undermine conservation efforts, making damage mitigation and compensation of special concern for wildlife conservation. However, the mechanisms underlying the occurrence of damage and claims at large scales are still poorly understood. Here, we investigated the patterns of damage caused by brown bears Ursus arctos and its ecological and socio‐economic correlates at a continental scale. We compiled information about compensation schemes across 26 countries in Europe in 2005–2012 and analysed the variation in the number of compensated claims in relation to (i) bear abundance, (ii) forest availability, (iii) human land use, (iv) management practices and (v) indicators of economic wealth. Most European countries have a posteriori compensation schemes based on damage verification, which, in many cases, have operated for more than 30 years. On average, over 3200 claims of bear damage were compensated annually in Europe. The majority of claims were for damage to livestock (59%), distributed throughout the bear range, followed by damage to apiaries (21%) and agriculture (17%), mainly in Mediterranean and eastern European countries. The mean number of compensated claims per bear and year ranged from 0·1 in Estonia to 8·5 in Norway. This variation was not only due to the differences in compensation schemes; damage claims were less numerous in areas with supplementary feeding and with a high proportion of agricultural land. However, observed variation in compensated damage was not related to bear abundance. Synthesis and applications . Compensation schemes, management practices and human land use influence the number of claims for brown bear damage, while bear abundance does not. Policies that ignore this complexity and focus on a single factor, such as bear population size, may not be effective in reducing claims. To be effective, policies should be based on integrative schemes that prioritize damage prevention and make it a condition of payment of compensation that preventive measures are applied. Such integrative schemes should focus mitigation efforts in areas or populations where damage claims are more likely to occur. Similar studies using different species and continents might further improve our understanding of conflicts arising from wildlife damage.